KNOWLEDGE MANAGEMENT MATURITY ASSESSMENT OF PT KASUARI - Arif Maulana, Omar
PT KASUARI is a transportation company specializes in air transport focusing on the low to medium segment of the market. They operate several types of aircraft to cater to market demand and able to operate in different market types. The problem however is that some of the employees are aging and due to the COVID-19 pandemic where transportation industry is one of the most severely impacted, the threat of employee departure due to various reason become higher. This brings forth the needs of a knowledge management practice to avoid knowledge loss on the company, thus allowing the company to sustain their competitive advantage.